Efektivitas Penerapan Metode Kaidah Dan Tarjamah (Taariqah Al-Qawa’id Wa Al Terjamah) Pada Pembelajaran Bahasa Arab Di Pondok Pesantren Darul Arqam Muhammadiyah Garut - Ramdhani, Zahrotur Rohmah (Program Studi Pendidikan Bahasa Arab, 2025)
Tariqah Al-Qawa'id Wa Al Tarjamah is a traditional (classical) language teaching method that emphasizes reading and translating aspects coupled with analysis of the grammatical structure contained in the text. Effectiveness of Implementing the al Qawaid Wa al Tarjamah Method in Increasing the Maharah Qira'ah of Class VIII Female Students at MTs Darul Arqam Muhammadiyah Garut. This research uses a type of quantitative research with a pre-experimental method which aims: 1) To find out the application of the al Qawaid Wa al Tarjamah method in increasing the maharah qira'ah of Class VIII Female Students at MTs Darul Arqam Muhammadiyah Garut. 2) Knowing the effectiveness of applying the al qawaid wa al tarjamah method in increasing the maharah qira'ah of Class VIII Female Students at MTs Darul Arqam Muhammadiyah Garut. Because there are quite significant values, it can be concluded that the application of the Al Qawaid Wa Al Tarjamah method is effective in increasing the maharah qira'ah of Class VIII Female Students at MTs Darul Arqam Muhammadiyah Garut. Keywords: Effectiveness, Tariqah Al-Qawa'id Wa Al Terjamah, Arabic Language Learning.